2008
DOI: 10.1186/1471-2148-8-4
|View full text |Cite
|
Sign up to set email alerts
|

Purifying selection and birth-and-death evolution in the class II hydrophobin gene families of the ascomycete Trichoderma/Hypocrea

Abstract: BackgroundHydrophobins are proteins containing eight conserved cysteine residues that occur uniquely in mycelial fungi. Their main function is to confer hydrophobicity to fungal surfaces in contact with air or during attachment of hyphae to hydrophobic surfaces of hosts, symbiotic partners or themselves resulting in morphogenetic signals. Based on their hydropathy patterns and solubility characteristics, hydrophobins are divided into two classes (I and II), the latter being found only in ascomycetes.ResultsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 68 publications
6
79
0
2
Order By: Relevance
“…Interestingly, the three corresponding genes, TmelHYD1, TmelHYD2 and TmelHYD3, are all located on the same scaffold (scaffold_3). Class II hydrophobins seems to be absent in T. melanosporum, unlike other Ascomycetes (Kubicek et al 2008). All the putative T. melanosporum hydrophobin sequences had a predicted signal peptide, and a hydrophobin/HYDRO domain was recognized by means of InterProScan (not shown).…”
Section: Other Cell Wall and Secreted Proteinsmentioning
confidence: 91%
“…Interestingly, the three corresponding genes, TmelHYD1, TmelHYD2 and TmelHYD3, are all located on the same scaffold (scaffold_3). Class II hydrophobins seems to be absent in T. melanosporum, unlike other Ascomycetes (Kubicek et al 2008). All the putative T. melanosporum hydrophobin sequences had a predicted signal peptide, and a hydrophobin/HYDRO domain was recognized by means of InterProScan (not shown).…”
Section: Other Cell Wall and Secreted Proteinsmentioning
confidence: 91%
“…Concerted evolution and birth-and-death evolution can be easily distinguished by analysis of genes from many pairs of closely related species (Nei et al 2000). The high level of the proportion of synonymous nucleotide differences per synonymous site (p S ) relative to the proportion of non-synonymous differences per non-synonymous site (p N ) between the individual members is diagnostic for birthand-death evolution (Kubicek et al 2008;Nei et al 2000;Piontkivska et al 2002). We then calculated the mean p S and p N values from intraspecific monomers using the DnaSP (Librado and Rozas 2009).…”
Section: Phylogenetic and Sequence Analysesmentioning
confidence: 99%
“…On the other hand the N-terminal regions, corresponding to the putative signal peptides, were highly hydrophobic as expected. Structure models were also obtained with Swiss Model using the HFBII protein from Trichoderma reesei (PDB ID 1R2M) as template, and showed that all the GEO1 proteins analysed had an a-helix, four antiparallel b-sheets and four loops (data not shown), coherently with the general structure of hydrophobins determined so far (de Vocht et al 1998;Hakanp€ a€ a et al 2004;Kubicek et al 2008).…”
Section: Analysis Of the Deduced Geo1 Proteins In Geosmithia Speciesmentioning
confidence: 77%
“…This process generates groups of functionally similar paralogous proteins, offered to natural selection (Nei et al 2000;Nei & Rooney 2005;Jiang et al 2006). Such a mechanism is prominent in the evolution of fungal hydrophobins, as was found in Trichoderma (Kubicek et al 2008), Paxillus (Rajashekar et al 2007) and Phlebiopsis (Mgbeahuruike et al 2012). As we showed, the GEO1 sequences from unrelated Geosmithia species can be very similar, a finding that can be ascribed to strong purifying selection.…”
Section: Resultsmentioning
confidence: 99%